PENGARUH KOMITMEN KARYAWAN DAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP KINERJA PEMERINTAH DAERAH DI KOTA PASURUAN - Temasmi Meriem Permatasari; Didied Poernawan A (Jurnal Ilmiah Mahasiswa FEB, 2013)
The objective of this study is to know the influence of employee commitment and internal control system to performance of regional government in Pasuruan City. The population of this study in 25 regional offices with a sample of 75 respondents Research method is quantitative descriptive. Therefore, data collection technique is survey approach. Result of research indicates that employee commitment and implementation government internal control system are positive significant influencing on performance of regional government in Pasuruan City. It is also found that employee commitment and implementation government internal control system have positive correlation and significant influence with performance of regional government in Pasuruan City. The implication of this research is relevant to regional government in Pasuruan City in order to pay more attention to the employee commitment factor and internal control system. Regional government are expected to be more maintain and increase performance of regional government that have implemented in Pasuruan City. Keywords:      employee commitment, government internal control system, performance government of regional